Penanganan Marine Growth Prevention System Guna Memperlambat Laju Korosi Pada Sistem Pipa Pendingin Air Laut di MT. Gas Dream - Maulana Nurdin , Muaffak Salam; Ali Muktar Sitompul; Pritha Kurniasih (Indonesian Journal of Marine Engineering, 2024)
The Marine Growth Prevention System (MGPS) is a crucial ship system that prevents the growth of marine organisms, which can cause corrosion to the structure. Marine growth can also narrow pipe diameters, increase pressure, and damage exposed structures if not properly managed. Identifying delays in seawater flow from the MGPS is key to maintaining the integrity of the seawater cooling system on the MT. Gas Dream. This study used qualitative methods. Data analysis and information processing from various sources such as observations, interviews, and case studies. By grouping and selecting data, significant elements are determined to be used as the basis for investigation. The results of the analysis are evaluated to obtain easy-to-understand conclusions. This study used the Root Cause Analysis method with tree diagrams for triangulation of data sources and information validation. This study aims to determine the causes and efforts of the slow flow of seawater coming out of MGPS. The results showed that the cause of the slow flow of seawater coming out of MGPS was because the reaction tank was dirty, the electrodes were full of crystals, the MGPS exit pipe was dirty, and the injection nozzle was blocked. The presence of obstacles such as mud and marine life can affect the slow flow of seawater, leading to the sea chest. In addition, the buildup of crystals on the electrodes can affect the electrolysis process which can cause marine life to grow. Therefore, routine checking and cleaning of MGPS components such as tanks, electrodes, MGPS pipes is the key in minimizing the risk of slow flow of seawater coming out of MGPS. To maintain MGPS performance, checking at least once a month on each MGPS component must be carried out to prevent the slow flow of seawater coming out of MGPS. Marine Growth Prevention System (MGPS) adalah sistem penting dalam kapal yang mencegah pertumbuhan biota laut yang dapat menyebabkan korosi pada struktur. Pertumbuhan biota laut juga dapat menyempitkan diameter pipa, meningkatkan tekanan, dan merusak struktur bangunan yang terpapar langsung dengan air laut tanpa penanganan yang tepat. Identifikasi keterlambatan aliran air laut dari MGPS menjadi kunci untuk menjaga integritas sistem pendingin air laut di MT. Gas Dream. Pada penelitian ini menggunakan metode kualitatif. Analisis data dan pengolahan informasi dari berbagai sumber seperti observasi, wawancara, dan studi kasus. Melalui pengelompokkan dan seleksi data, elemen yang signifikan ditentukan untuk digunakan sebagai dasar penyelidikan. Hasil analisis dievaluasi untuk mendapatkan kesimpulan yang mudah dipahami. Penelitian ini menggunakan metode Root Cause Analysis dengan tree diagram untuk triangulasi sumber data dan validasi informasi. Tujuan dari penelitian ini adalah untuk mengetahui penyebab dan upaya lambatnya aliran air laut yang keluar dari MGPS. Hasil penelitian menunjukan bahwa penyebab lambatnya aliran air laut yang keluar dari MGPS karena reaction tank kotor, elektroda penuh dengan kristal, pipa out MGPS kotor, dan injection nozzle tersumbat. Adanya hambatan seperti lumpur dan biota laut dapat mempengaruhi lambatnya aliran air laut yang menuju ke sea chest. Selain itu, penumpukan kristal pada elektroda dapat mempengaruhi proses elektrolisis yang dapat menyebabkan biota laut dapat tumbuh. Oleh karena itu, pengecekan serta pembersihan yang rutin pada komponen MGPS seperti tank, elektroda, pipa MGPS menjadi kunci dalam meminimalisir resiko lambatnya aliran air laut yang keluar dari MGPS. Untuk mempertahankan performa MGPS, pengecekan minimal satu bulan sekali pada setiap komponen MGPS harus dilakukan agar mencegah terjadinya lambatnya aliran air laut yang keluar dari MGPS.